Analisis Minat Generasi Milenial Kota Samarinda dalam Investasi di Pasar Modal Syariah - Hasanudin, Maulana; Mursyid, Mursyid (El-kahfi | Jurnal Ekonomi Islam, 2024)
Investment in the capital market has developed significantly and has reached various segments of society. This includes the millennial generation, who possess good financial literacy and are now engaging in the capital market, particularly in Islamic capital markets. This research aims to assess the interest of the millennial generation in Samarinda in investing in Islamic capital markets. The study employs a qualitative research method with data collection through surveys. Data was gathered from a sample of 100 millennials in Samarinda, aged 28-44 years, who invest in Islamic capital markets. The findings indicate that the interest of millennials in Samarinda in investing in Islamic capital markets is quite high, with a score of 68.11%. The motivating factors include self-awareness, social support, and emotional security. To enhance millennial participation, strategies should focus on Islamic financial literacy, providing relevant investment products, and strengthening community engagement through events and discussion forums. By implementing these measures, millennial participation in Islamic capital markets can increase, supporting the growth of the Islamic economy in the region.